The Romanian coastal area and green transport infrastructure - Nică Flaviu Ioan (E3S Web of Conferences)
The first part of the paper presents the local transport infrastructure conditions of the Romanian Coastal Area. The Coastal Area, from the geographical point of view is located on the East and South - East of the country, being part of South – East Development Region. It is aggregated mainly in two counties, Tulcea, where is found the intersection of Danube with Black Sea in Danube Delta and, Constanta where is the entire Romanian Black Sea shoreline. The first part also presents the steps that are already made by Romanian authorities to ensure the sustainability and reduce the pollution by increasing the green transport infrastructure. The second part of the paper presents the analysis of the transport system in the region together with the supporting data, and the challenges that puts pressure on our coastal area. Finaly, the aim is to come with solutions in order to increase sustainability, climate resilience, and to reduce the vulnerability on our coastal area with the purpose of multiplying and creating a good practice example for the entire community.